Letter : Invitation to British women to visit Spain - Stolz, George
012a-0033-001 INTERNATIONAL FEDERATION OF TRADE UNIONS St/H TELEGRAMS INTERFED-PARIS TELEPHONE INVALIDES 45-88 9, AVENUE D'ORSAY. PARIS-VII EXECUTIVE COMMITTEE : President : W. M Citrine. Great Britain Vice-Presidents: H. Jacobsen, Denmark ; L. Jouhaux, France ; E Kupers, Holland; Corn. Mertens, Belgium ; R Tayerle, Czechoslovakia General Secretary : W Schevenels Affiliated countries ARGENTINE AUSTRIA BELGIUM CANADA CZECHOSLOVAKIA DENMARK DUTCH EAST INDIES ESTONIA FINLAND FRANCE GREAT BRITAIN GREECE HOLLAND HUNGARY INDIA LUXEMBURG MEMEL TERRITORY MEXICO NORWAY PALESTINE POLAND ROUMANIA SOUTH AFRICA SOUTH-WEST AFRICA SPAIN SWEDEN SWITZERLAND YUGOSLAVIA Letter No. _. 2nd November, 1938. Mr. Walter M. Citrine, LONDON. Dear Comrade Citrine, INVITATION TO BRITISH WOMEN TO VISIT SPAIN With reference to our letter of the 17th September last, we have now received a reply from the UGT about the Barcelona liaison Committee and the Women's Groups in the Iron and Steel Trade Unions. The UGT says that "as these bodies are independent of our own Trade Union Movement, being simply organs of liaison between the two Trade Unions Movements they are not competent to send such invitations abroad. When it is a matter of inviting organisations which are within the IFTU, all powers in the matter of invitation must rest with our National Trade Union Centre." Yours sincerely, G. Stolz Assistant Secretary: 292/946/12a/33